Application of selected methods of intellectual capital valuation based on Grupa Kapitałowa Żywiec SA - Adamska, Małgorzata (Zastosowanie wybranych metod wyceny kapitału intelektualnego na przykładzie Grupy Kapitałowej Żywiec SA, 2019)
The article presenting literature overview focuses on the legal framework of the analysis, reporting and valuation of intangible assets identified in contemporary companies within their intellectual capital. The research part of the article is focused on the practical applications of selected methods of intellectual capital valuation based on Grupa Kapitałowa Żywiec SA corporate group, which has been keeping publicly available non-financial reports since 2017. The purpose of this article is to show that the process of intellectual capital valuation requires the long-term integration of selected valuation methods as well as the consideration of the context of the analysed numbers. The methods selected for the purposes of this presentation are: price/book value index, Tobin’s q ratio, calculated intangible value index and value added intellectual coefficient. The intellectual capital valuation carried out for the purposes of this article has confirmed that applying only one valuation method does not give a fair view of intangible assets, and the lack of considering context in the valuation makes the obtained data lose its decision-making value
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 8, s. 167-178
Keywords: intellectual capital; MV/BV; Tobin's q ratio; CIV; VAIC; kapitał intelektualny; współczynnik q-Tobina